Maternal supply of cysteamine alleviates oxidative stress and enhances angiogenesis in porcine placenta - Shuangbo Huang; Zifang Wu; Zihao Huang; Xiangyu Hao; Longmiao Zhang; Chengjun Hu; Jianfu Wei; Jinping Deng; Chengquan Tan (Journal of Animal Science and Biotechnology, 2021)
Abstract Background Oxidative stress in placenta is associated with the occurrence of adverse pregnancy outcomes in sow, but there are few satisfactory treatment strategies for these conditions. This study investigated the potential of cysteamine (CS) as an antioxidant protectant for regulating the reproductive performance, redox status, and placental angiogenesis of sows. Methods The placental oxidative stress status and vascular density of piglets with different birth weights: < 1.0 kg (low birth weight, LBW) and 1.4–1.6 kg (normal birth weight, NBW) were evaluated, followed by allotting 84 sows to four treatments (n = 21) and feeding them with a basal diet supplemented with 0, 100, 300, or 500 mg/kg of CS from d 85 of gestation to d 21 of lactation, respectively. Placenta, serum, and colostrum samples of sows or piglets were collected, and the characteristics of sows and piglets were recorded. Furthermore, the in vivo results were validated using porcine vascular endothelial cells (PVECs). Results Compared with the NBW placentae, the LBW placentae showed increased oxidative damage and were vulnerable to angiogenesis impairment. Particularly, H2O2-induced oxidative stress prompted intracellular reactive oxygen species generation and inhibited the tube formation and migration of PVECs as well as the expression of vascular endothelial growth factor-A (VEGF-A) in vitro. However, dietary CS supplementation can alleviate oxidative stress and improve the reproductive performance of sows. Specifically, compared with the control group, dietary 100 mg/kg CS could (1) decrease the stillbirth and invalid rates, and increase both the piglet birth weight in the low yield sows and the placental efficiency; (2) increase glutathione and reduce malondialdehyde in both the serum and the colostrum of sows; (3) increase the levels of total antioxidant capacity and glutathione in LBW placentae; (4) increase the vascular density, the mRNA level of VEGF-A, and the immune-staining intensity of platelet endothelial cell adhesion molecule-1 in the LBW placentae. Furthermore, the in vitro experiment indicated that CS pre-treatment could significantly reverse the NADPH oxidase 2-ROS-mediated inactivation of signal transducer and activator of transcription-3 (Stat3) signaling pathway induced by H2O2 inhibition of the proliferation, tube formation, and migration of PVECs. Meanwhile, inhibition of Stat3 significantly decreased the cell viability, tube formation and the VEGF-A protein level in CS pretreated with H2O2-cultured PVECs. Conclusions The results indicated that oxidative stress and impaired angiogenesis might contribute to the occurrence of LBW piglets during pregnancy, but CS supplementation at 100 mg/kg during late gestation and lactation of sows could alleviate oxidative stress and enhance angiogenesis in placenta, thereby increasing birth weight in low yield sows and reducing stillbirth rate. The in vitro data showed that the underlying mechanism for the positive effects of CS might be related to the activation of Stat3 in PVECs.